Case study on cleaner production in food processing industry : pineapple cannery - 272609 Azman Jaafar (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2003